Proteome of the degenerating retina - LéveillardThierry (眼科学报; 卷 31, 编号 2 (June 2016): 《眼科学报》, 2016)
In the last issue of the Journal of Proteome Research , Ly et al . (1) communicate on their kinetic analysis of the proteome of the rd10 mouse, a model of inherited retinal blindness. Why this study is so important for our understanding of retinal diseases?